Pengaruh Konsentrasi Asam Sulfat (H₂So₄) pada Proses Hidrolisis Lignoselulosa Batang Kelapa Sawit Terhadap Kadar Gula Terlarut dan Gula Reduksi - Asylih Za’rara Hasibuan; Heri Purwanto (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Oil palm plantations produce solid biomass, one of which is the oil palm trunk, which contains cellulose. The cellulose content in oil palm trunks has the potential to produce bioethanol if processed through hydrolysis to break down polysaccharides into sugars. The objective of this study was to determine the effect of varying sulfuric acid (H₂SO₄) concentrations on the hydrolysis process for producing fermentable sugars from oil palm trunk substrate. The study design employed a Non-Factorial Complete Randomized Design consisting of 3 treatment levels—variations in H₂SO₄ concentration (1 M, 2 M, 3 M)—each with 3 replicates (for a total of 9 samples). Statistical analysis utilized ANOVA and Duncan’s post-hoc test at a 95% confidence level. Dissolved sugar content was measured using a refractometer (% Brix), while reducing sugar was determined using the Nelson-Somogyi method with a UV-Vis spectrophotometer at a wavelength of 540 nm. The hydrolysis was conducted at 90°C for 100 minutes. The highest sugar concentration was obtained from the 3 M treatment, at 18.80% Brix with a reducing sugar content of 428.54 ppm. Duncan’s test showed that the 3 M concentration differed significantly from 1 M (310.71 ppm) and 2 M (340.23 ppm), while 1 M and 2 M did not differ significantly. In conclusion, a 3 M H₂SO₄ concentration is the optimal condition for the hydrolysis of oil palm stems, yielding a significantly higher reducing sugar content.